Inside Front Cover: Volume 2 Issue 2. (29th June 2021) - Xu, Jie; Cui, Xiaoya; Liu, Nan; Chen, Yanan; Wang, Hong‐Wei
Abstract : Inside front cover image : The revolutionary improvement of hardware and algorithm in cryogenic electron microscopy (cryo‐EM) has made it a routine method to obtain structures of macromolecules at atomic resolution. 2D nanomaterials with high electronic conductivity and ultrathin thickness are explored as promising cryo‐EM specimen supporting films. In this review, the authors summarized the structural engineering of graphene as the supporting films for cryo‐EM grids. The structurally engineered graphene possessed good conductivity, mechanical strength, selectivity on target macromolecules, hydrophilicity, and negligible background noise. Moreover, the adoptions of graphene on high‐resolution cryo‐EM imaging, cryogenic electron tomography (cryo‐ET) reconstruction, and graphene liquid cell (GLC) are systematically introduced here. The authors believe the structurally engineered graphene as well as other 2D materials will broaden the application of high‐resolution cryo‐EM and significantly promote the methodology development. (DOI: https://doi.org/10.1002/smm2.1045 )